ASUPAN MAKANAN ANAK BALITA GIZI KURANG DI JORONG MANGGOPOH DALAM NAGARI ULAKAN TAPAKIS KABUPATEN PADANG PARIAMAN - Suryati, Novi; Elida, Elida; Fridayati, Lucy (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This research is conducted because the phenomenon of children who get less nutrientcalled malnutrition at Manggopoh Dalam Nagari Ulakan Tapakis Padang Pariaman Regency.The purpose of this research is to describe how the providing food of malnutrition children. Itis a kind of descriptive qualitative research which the source of the data is gotten frommothers who has the children in undernutrition. The sampling technique usedin this resesrchis snowball sampling. The data isi collected by doing observations, interviews anddocumentations. The result of the research shows that (1) there is no variation menu given tothe children and there is unbalanced food supply with the nutrition need (2) the frequent ofeating are breakfast about 8.am to 10.30 am, Lunch is about 1pm-3pm ang not all theinformantget dinner for the children (3) food supply consist of 100-200 gr of carbohydrate,50-100 gr protein, 50-100 gr vitamins and 200cc of mineralKeyword: Providing Food of Malnourished Children